2021
DOI: 10.1177/0272684x211022176
|View full text |Cite
|
Sign up to set email alerts
|

Where Do We Go After Surviving the Virus? Cross-Country Documentary Analysis of the Social Consequences Faced by COVID-19 Survivors

Abstract: In this study, we attempted to move beyond the skewed discussions on stigma to unravel other social consequences that are experienced by persons who have recovered from COVID-19. We conducted a documentary review of published news reports from 14 highly ranked news portals in Ghana and Malaysia (published between 1st January 2020 and 30th August 2020) that contained personal accounts from the recovered patients about their lived experiences with the virus and social consequences encountered after recovery. Nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The measures developed during the pandemic on infection and disease prevention are currently observed by 80% of survey participants. Wearing masks in public places, hand and surface sanitation, social distancing and other measures have firmly come into the life of society and have become commonplace [24].…”
Section: Resultsmentioning
confidence: 99%
“…The measures developed during the pandemic on infection and disease prevention are currently observed by 80% of survey participants. Wearing masks in public places, hand and surface sanitation, social distancing and other measures have firmly come into the life of society and have become commonplace [24].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the dissemination of this information in the community should be discouraged and community support should be provided ( 39 ). If COVID-19 survivors and their families are at risk of physical attacks in the community, policies and regulations to protect them should also be developed and improved ( 40 ). But simply encouraging intergroup contact and communication seems less effective in reducing stigma ( 35 ).…”
Section: Current Study On Stigmatization Of Covid-19 Survivorsmentioning
confidence: 99%
“…The social care system is a critical component of our social infrastructure, and the pandemic has highlighted the cost of neglecting it. Presently, social care policies that address stigma mostly focus on the healthcare sector, such as promoting public health knowledge, strengthening the psychological resilience of COVID-19 survivors, and correcting attitudes toward the virus ( 14 , 32 , 40 ). However, research has suggested that social support is necessary to eradicate stigma, but it has not yet revealed the social mechanisms of stigma or how to eliminate it from the perspective of social power inequality ( 25 , 39 ).…”
Section: Marxist Criticism On Stigmatization Of Covid-19 Survivorsmentioning
confidence: 99%
“…One factor that has played a substantial role in public health practitioners’ influence during the COVID-19 pandemic has been stigma. Studies have begun to look at the experiences of stigma among people who have tested positive for SARS-CoV-2 in countries outside the United States ( Chew et al, 2021 ; Iqbal et al, 2021 ; Owusu et al, 2021 ; Theano et al, 2020 ; Yuan et al, 2021 ). However, there has been relatively little investigation into the role of stigma in health behavior change in the United States, where the pandemic has been highly politicized and polarizing ( Rabin & Dutra, 2021 )—especially in the early days of the pandemic, when the societal response was still in a formative phase.…”
mentioning
confidence: 99%